Reward Deficiency Syndrome (RDS): A Common Neurogenetic Trait/State of All Addictions: Is this the new DSM? - Blum, Kenneth; Lewandrowski, Kai Uwe; Lorio, Morgan P.; Pinhasov, Albert; Mohankumar, Kavya; Sharafshah, Alireza; Thanos, Panayotis K.; Bowirrat, Abdalla; Lindeau, Marco; Dowling, Álvaro; Dowling, Rafaela; Bergamaschi, Joao Paulo; et al. (British Journal of Healthcare and Medical Research, 2026)
Steven Hyman, former director of the NIMH (2012), noted that neuroscience studies of psychiatric disorders often rely on definitions from the Diagnostic and Statistical Manual of Mental Disorders (DSM), which treats conditions as distinct entities. However, boundaries between disorders are less strict than DSM categories suggest. To address this, Hyman’s group introduced the Research Domain Criteria (RDoC) project, which defines five brain-based domains impaired across psychiatric conditions. Similarly, Blum (1995) proposed Reward Deficiency Syndrome (RDS) as a unifying framework for substance and non-substance addictive behaviors. Currently, over 1,650 PubMed studies link to “reward deficiency,” and 281 specifically to RDS. Recent GWAS and pharmacogenomic (PGX) studies in 88.8 million subjects support dopamine dysregulation as the accurate phenotype of RDS. The Genetic Addiction Risk Severity (GARS®) test has been developed as a predictor of RDS and preaddiction. Psychiatric disorders identified in the DSM-5 share many genetic polymorphisms, often tied to dopaminergic signaling. We propose a biphasic prevention and treatment model for addictions (alcohol, nicotine, glucose, etc.). Acute harm reduction should target postsynaptic Nucleus Accumbens (NAc) dopamine receptors (D1–D5), while long-term therapy should promote dopamine activation/release at the NAc. Failure to balance these may lead to mood instability, aberrant behavior, or suicidal ideation. Individuals with serotonergic/dopaminergic receptor deficits or high COMT activity may self-medicate with substances and behaviors that release dopamine. Evidence suggests that upregulating D2 receptors in genetically vulnerable individuals could mitigate addictive risk. While in vivo D2 agonists downregulate receptors, in vitro studies show constant stimulation can promote receptor proliferation. Gene therapy inducing DRD2 overexpression reduces alcohol and cocaine craving in rodents. Natural dopaminergic repletion therapy may provide a safe, long-term strategy to restore dopaminergic function, improve recovery, and enhance quality of life in RDS-related behaviors. WC 286